Risk management for nonprofits: How to enhance success - Santos, M.; Laureano, R. (IMA Educational Case Journal, 2024)
THIS CASE AIMS TO CONTRIBUTE TO students’ understanding of how a preassessment of the potential for accomplishing social impact goals can be conducted using a risk management framework. For this purpose, the case presents a daycare center (DCC) project the nonprofit Action for Development—Association of Seniors (ADAS) implemented and focuses on beneficiary acceptance, transportation, and hygiene a...